Multidimensional Lewis Acidity: a consistent data set of chloride, hydride, methide, water and ammonia affinities for 183 p-block element Lewis Acids - Erdmann, Philipp; Greb, Lutz (ChemPhysChem, 2021)
The computed fluoride ion affinity (FIA) is a widely applied descriptor to gauge Lewis acidity. Like every other single-parameter Lewis acidity scale, the FIA metric suffers from the one-dimensionality, that prohibits addressing Lewis acidity by the multidimensionality it inherently requires (i. e., reference Lewis base dependency). However, a systematic screening of computed affinities other than the FIA is much less developed. Herein, we extended our CCSD(T)/CBS benchmark of different density functionals and the DLPNO-CCSD(T) method for chloride (CIA), methide (MIA), hydride (HIA), water (WA), and ammonia (AA) affinities. The best performing methods are subsequently applied to yield nearly 800 affinities for 183 p-block element compounds of group 13-16 with an estimated accuracy of <10 kJ mol−1. The study‘s output serves as a consistent library for qualitative analyses and a training set for future statistical approaches. A first holistic correlation analysis underscores the need for a multidimensional description of Lewis acidity.